Răspuns :
M + P + POR= 100
m + p = 73
p + por= 63
inlocuim in prima expresie
73 + por = 100
por = 100 - 73
por = 27
p + por = 63
p + 27 = 63
p = 63 - 27
p = 36
m + p = 73
m + 36 = 73
m = 73 - 36
m = 37
verificam
m + p + por = 37 + 36 + 27 = 100
m + p = 73
p + por= 63
inlocuim in prima expresie
73 + por = 100
por = 100 - 73
por = 27
p + por = 63
p + 27 = 63
p = 63 - 27
p = 36
m + p = 73
m + 36 = 73
m = 73 - 36
m = 37
verificam
m + p + por = 37 + 36 + 27 = 100
notam cu M-mere, PE - pere si PO-portocale
M+PE+PO=100
73=M+PE ⇒M=73-PE
63=PE+PO ⇒PO=63-PE
inlocuim M si PO in prima ecuatie si ⇒ 73-PE+PE+63-PE=100
136-100=PE⇒ PE=36
dar M=73-PE=73-36=37⇒ M=37
si PO=63-PE=63-36=⇒ PO=27
verificare
M+PE+PO=100 37+36+27=100
M+PE+PO=100
73=M+PE ⇒M=73-PE
63=PE+PO ⇒PO=63-PE
inlocuim M si PO in prima ecuatie si ⇒ 73-PE+PE+63-PE=100
136-100=PE⇒ PE=36
dar M=73-PE=73-36=37⇒ M=37
si PO=63-PE=63-36=⇒ PO=27
verificare
M+PE+PO=100 37+36+27=100